2021
DOI: 10.3390/app11062699
|View full text |Cite
|
Sign up to set email alerts
|

Proportional Double Derivative Linear Quadratic Regulator Controller Using Improvised Grey Wolf Optimization Technique to Control Quadcopter

Abstract: A hybrid proportional double derivative and linear quadratic regulator (PD2-LQR) controller is designed for altitude (z) and attitude (roll, pitch, and yaw) control of a quadrotor vehicle. The derivation of a mathematical model of the quadrotor is formulated based on the Newton–Euler approach. An appropriate controller’s parameter must be obtained to obtain a superior control performance. Therefore, we exploit the advantages of the nature-inspired optimization algorithm called Grey Wolf Optimizer (GWO) to sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The test results show that our approaches proved more effective in a number of aspects such as: (i) A 9 DOF IMU is potentially better than a 6 DOF IMU in the article [16] because it can use sensor fusion (mixing the data from different sensors) in order to improve the quality of the final output (ii) We have added to the model both low feeding rate and high-frequency Gaussian white noise instead of only high feeding rate as in the test of the article [40]. This increased the accuracy of the test results…”
Section: Developments Of the Quadrotor Modelmentioning
confidence: 99%
“…The test results show that our approaches proved more effective in a number of aspects such as: (i) A 9 DOF IMU is potentially better than a 6 DOF IMU in the article [16] because it can use sensor fusion (mixing the data from different sensors) in order to improve the quality of the final output (ii) We have added to the model both low feeding rate and high-frequency Gaussian white noise instead of only high feeding rate as in the test of the article [40]. This increased the accuracy of the test results…”
Section: Developments Of the Quadrotor Modelmentioning
confidence: 99%
“…Almost all the finding flight responses of quadcopter four motions noticeably improved due to the proposed PD2LQR as an alternative controller. Shauqee et al [17] controlled altitude and attitude responses demonstrated by a quadrotor vehicle. The PD2-LQR was used with an improved grey wolf optimiser (IGWO) to search for an appropriate controller parameter for superior control performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, authors [3, 12−20] used the classical LQR to control general aviation A/C, B747-100, quadcopter and rider-less bicycles for real limited scenarios. Some of those [13,[16][17]19] proposed the so-called FI-LQR, R-LQR, P-LQR, PD-LQR, PD2-LQR and IGWO-PD2LQR (Modified LQR versions) to ensure the LQR shortcomings not influencing the performance under unstandardised conditions. Shauqee et al [17] argued that IGWO-PD2LQR showed more pronounced outperformance than the other controllers" responsiveness.…”
Section: Welstead and Crousementioning
confidence: 99%
See 2 more Smart Citations